ALAṀKARA DALAM KAKAWIN WIRASATING WONG KAKUNG: TINJAUAN STILISTIKA - I Putu Gede Wahyu Hermawan (ADISAM PUBLISHER, 2026)
This article discusses sabdalāṁkara in the kakawin titled Wirasating Wong Kakung. The theoretical framework used is stylistics, or the study of language style, which is commonly applied to poetic literary works. Kakawin itself is a form of Old Javanese poetry, and within this tradition, stylistic elements are referred to specifically as alaṁkara. This study identifies two main types of alaṁkara: sound-based devices (sabdalāṁkara) and meaning-based devices (arthalāṁkara). However, not all types of these stylistic devices are found in the text. The sabdalāṁkara elements identified include padayamaka, kanciyamaka, and wrĕtayamaka. Meanwhile, the arthalāṁkara elements found are rupaka, wyatireka, upareksa, wisosekti, and arthāntaranyasa. The presence of these alaṁkara contributes significantly to the aesthetic quality of the kakawin, enhancing its beauty both in written form and when performed through traditional recitations such as matembang and mababasan.